“You Can See How Things Will End by the Way They Begin”: The Contribution of Early Mutual Obligations for the Development of the Psychological Contract - Farnese, Maria Luisa; Livi, Stefano; Barbieri, Barbara; Schalk, René (Frontiers in Psychology, 2018)
This study explores dynamic processes in the development of the psychological contract, focusing on the interaction of obligations related to the two parties (i.e., employees’ perceptions of both their own and the organisation’s obligations fulfilment) on attitudinal outcomes (organisational commitment and turnover intention) during the initial stage of the employment relationship. In a twofold cross-sectional and two-wave study on newly hired correctional police officers, we examined: a) whether perception of organisational obligations fulfilment moderates the relationship between employee obligations and their attitudes (Study 1, n.500); b) the direct and moderated influence of perceived obligations at the entrance stage on those in the following months (Study 2, n.223). Results confirmed that, in the eyes of the newcomer, the obligations fulfilment of each of the two parties interact, having an additional effect beyond the main direct effects, in influencing both subsequent obligations perceptions and, through this, the outcome variables. Theoretical and practical implications of the findings are discussed.